Hadith #6501 - Sahih Muslim - Abu Moosa (Sahih Muslim)
When any one of you happens to go to a meeting or the bazar with an arrow in his hand he must grasp its pointed head; then (he again said): He must grasp its pointed head. Abu Musa said: By Allah, we did not court death until some of us had flung arrows upon the faces of one another.
Grade: Sahih